The Dietary Approaches to Stop Hypertension Diet and New and Recurrent Root Caries Events in Men. Issue 9 (17th August 2015) - Kaye, Elizabeth K.; Heaton, Brenda; Sohn, Woosung; Rich, Sharron E.; Spiro, Avron; Garcia, Raul I.
<x xml:space="preserve">Abstract</x> Objectives To examine the effect of overall dietary quality on number of teeth with new or recurrent root caries events during follow‐up (root caries increment). Design Prospective study with dental examinations approximately every 3 years over 20 years. Setting Veterans Affairs Dental Longitudinal Study in greater Boston, Massachusetts, area. Participants Men aged 47 to 90 (N = 533). Measurements A single calibrated examiner assessed root caries and restorations, calculus, probing pocket depth, and attachment loss on each tooth at each examination. The adjusted root caries increment (root‐ADJCI) was computed from new and recurrent root caries events on teeth with recession of 2 mm or more. Dietary information was obtained from food frequency questionnaires. An adherence score was computed by comparing consumption frequency of 10 food groups (fruits, vegetables, total dairy, low‐fat dairy, meat, total grains, high‐fiber grains, legumes, fats, sweets) from the Dietary Approaches to Stop Hypertension (DASH) diet guidelines. Mean root‐ADJCIs were compared according to DASH adherence score quartile using generalized linear negative binomial regression models, controlling for age, number of teeth at risk of root caries, time at risk of root caries, calculus, presence of removable denture, history of dental prophylaxis, body mass index, and smoking status. Results Men with DASH adherence scores in the highest quartile had a 30% lower mean root‐ADJCI (1.86 teeth) than those in the lowest quartile (2.68 teeth) (P = .03). Root‐ADJCI was lower with greater adherence to recommendations for vegetables and total grains and greater with greater sugar‐sweetened carbonated beverage consumption. Root caries incidence rate did not vary significantly between quartiles. Conclusion A higher‐quality diet may reduce root caries risk in older men.